Method of osteosynthesis of trans- and supracondylar humeral fractures in children - Boskin, Hryhorii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Supra- and transcondilar fracture consist from 65.5 to 85.5 % out of distal humeral bone (HB) fractures. Transcondilar humeral fractures to supracondilar ratio — 15:1. Open reposition is recommended in a cases of unsuccessful conservative treatment and with T- and U-shaped fractures, open and complicated fractures. Minimal invasive osteosythesis is the most preferable technique. Purpose: to improve results of treatment of supra- and transcondilar HB fractures in children. Methods: open retrograde Kirschner wire fixation has been used for the open reposition of supra- and transcondilar fractures in children with the age of 3–12 years. Results: using the indicated fixation technique in all cases did not result in postoperative complication in all 10 cases, all wounds healed with primary tension. After the cast mobilization forming of bone regeneration revealed on radiographs. Elbow joint function repaired after the three months. proposed technique has the following advantages: 1) surgical approach through the septum intermusculare brachiі mediale allows to provide sufficient mobilization of the central fragment; 2) in spite of fracture features fixators ate introduced intramedullary in the defined plane and angle providing stable fixation of HB fragments. Conclusion: utilization of proposed method in a cases of of supra- and transcondilar HB fractures allows to achieve stable bone fragment fixation in spite of fractures plane. Stable fixation and relative fixation stability are the main advantages of the methods allowing to consider this tactic for the surgical treatment in patients with supra- and transcondilar humeral fracture.